Influence of the detonation-spraying mode on the phase composition and properties of Ni-Cr coatings - Maulet, M; Rakhadilov, B. K.; Sagdoldina, Zh. B.; Kassymov, A. B.; Kakimzhanov, D. N. (Eurasian Journal of Physics and Functional Materials, 2026)
In work considers the results of studies of the phase composition and mechanical-tribological properties of Ni-Cr detonation coatings obtained at different values of the volume of filling the detonation barrel with an explosive acetylene-oxygen mixture. Analysis of the obtained experimental results indicates that the phase composition and properties of detonation coatings strongly depend on the technological parameters of spraying. When the barrel is filled with an explosive gas mixture of 40%, the coating is not dense enough, with noticeable boundaries between individual particles, which may be the result of insufficient heating and acceleration of the particles of the sprayed powder. It is determined that when the volume of filling the detonation barrel with an explosive mixture is up to 60%, there is a widening and a decrease in the intensity of the main peaks. Higher values of microhardness were obtained at 50% filling of the barrel. The results of tribological tests of coatings showed that the coating applied when filling the detonation barrel with an explosive mixture of up to 60% has a lower coefficient of friction than other coatings. Recommended Citation Maulet, M.; Rakhadilov, B. K.; Sagdoldina, Zh. B.; Kassymov, A. B.; and Kakimzhanov, D. N. (2020) "Influence of the detonation-spraying mode on the phase composition and properties of Ni-Cr coatings," Eurasian Journal of Physics and Functional Materials: Vol. 4: No. 3, Article 7. DOI: https://doi.org/10.29317/ejpfm.2020040307